Bone Marrow Edema and Low Back Pain in Elderly Degenerative Lumbar Scoliosis: A Cross-Sectional Study. Issue 10 (May 2016) - Nakamae, Toshio; Yamada, Kiyotaka; Shimbo, Takuro; Kanazawa, Toshikatsu; Okuda, Teruaki; Takata, Haruhiko; Hashimoto, Takashi; Hiramatsu, Takeshi; Tanaka, Nobuhiro; Ochi, Mitsuo; Olmarker, Kjell; Fujimoto, Yoshinori
Abstract : Study Design: Cross-sectional study. Objective: To examine whether bone marrow edema is associated with low back pain in elderly patients with degenerative lumbar scoliosis. Summary of Background Data: The cause of low back pain in degenerative lumbar scoliosis is unclear. Methods: A total of 120 degenerative lumbar scoliosis patients 65 years of age or older were evaluated. Radiography, computed tomography (CT), magnetic resonance imaging (MRI), and tender point examination in the lumbar spine were performed. On MRI, coronal gadolinium-contrasted T1- or T2-weighed fat-saturated images were used to score the size of bone marrow edema. The prevalence of bone marrow edema in patients with and without low back pain was compared; in patients with low back pain, we tested whether the locations of lumbar tender point were consistent with that of bone marrow edema. Results: Bone marrow edema was found in 62 of 64 (96.9%) patients with low back pain compared with 21 of 56 (37.5%) patients without it ( P < 0.001). Bone marrow edema located more frequently on the concave side than on the convex side of scoliosis ( P < 0.001). Among patients with low back pain, bone marrow edema score was associated with low back pain severity ( r = 0.724; P < 0.001), and the location of lumbar tender point were consistent with that of bone marrow edema (κ value = 0.745; P < 0.001). Conclusion: Bone marrow edema on MRI was closely associated with the presence of low back pain in elderly degenerative lumbar scoliosis. Level of Evidence: 4